Juvenile Dermatomyositis Forty Years On: Case Report - Rego de Figueiredo, I (2018)
We present a case report of a 42 year old female, diagnosed at the age of 3 with Juvenile Dermatomyositis. The clinical course was severe and refractory to immunosuppressive therapy. Currently, she is mostly affected by severe muscle atrophy, large joint contractures, calcinosis, and a lipodystrophy associated metabolic syndrome with hypertriglyceridemia, insulin resistance, high total testosterone and hepatic steatosis. She developed Hodgkin´s lymphoma in the course of her disease. Personalized therapeutic choices are discussed as regards juvenile dermatomyositis complications.